Advances in communications-based train control systems - Yu, F. Richard (CRC Press, 2016)
This book presents the latest advances in communication-based train control (CBTC) research. Chapters cover different aspects of modelling, analysis, design, testing, management, deployment, and optimization of CBTC systems. Other topics include: background and evolution of train signaling/train control systems; features and architecture of CBTC systems and describes current challenges and successful implementations around the world; nondestructive testing techniques; wireless channel modelling techniques for underground tunnels and viaducts; advanced wireless communication systems to improve CBTC communication availability; schemes to integrate train control and train-ground communications by modelling the control system of a group of trains in CBTC as a networked control system; use of cognitive control to improve train control performance, considering both train, ground communication and train control. --